Nerovnosť finančných položiek hospodárenia slovenských domácností - Sipková, Ľubica; Sipko, Juraj (Univerzita Pardubice, 2017)
The paper describes the level and the relative inequality of households' finances by absolute and relative measures. The quantitative analysis covers eight NUTS III regions of the Slovak republic and compares relative inequality of the financial situation according to various subgroups of households. The analysis procedure uses the official individual data of the second wave of the Eurosystem's Household Finance and Consumption Survey (HFCS), which collects household-level data in the year 2014. At the beginning, the paper describes microdata and the methodology. Based on quantitative analysis mainly using quantile methods, what follows is a numerical and graphical comparison of statistical measures of households’ net wealth, total real assets and total liabilities of subgroups of Slovak households. Our study is focused mostly on concentration measurement and provides an inequality analysis of households’ finances with decomposition of Theil T measure of the components of households’ finances according to region, level of household’s reference person’s education and household types based on HFCS microdata of the Slovak Republic.
The inequality of slovak households' finances
Keywords: household; finance; net wealth; NUTS 3; Theil T index; inequality decomposition; HFCS; D10; D14; D31